A Case of Stage 4B Seromucinous Ovarian Borderline Tumor With Endometriosis and Review of the Literature. (March 2017) - Newton, Claire L.; Brockbank, Elly; Singh, Naveena; Faruqi, Asma
Abstract : Ovarian mucinous borderline tumors are traditionally divided into 2 morphologic groups: endocervical type, also known as seromucinous, and intestinal type. We present a case of stage 4B seromucinous ovarian borderline tumor with endometriosis and review the literature. At the time of writing, this is believed to be the first case of a seromucinous borderline tumor reported at such an advanced stage.